Analyzing the Influence of Online Testimonials and Celebrity Endorsements on Consumer Purchase Decisions for Pocari Sweat Isotonic Drinks - Wibowo, Agung Eko; Ambarwati, Dwi Asri Siti (Economics and Digital Business Review, 2025)
In today’s digital era, online testimonials and the role of influencers are increasingly important in influencing purchasing decisions. Purchasing decisions are an important focus for companies in formulating influential factors. The method used in this study was a survey by distributing questionnaires via Google Form to 45 respondents who were consumers who had consumed Pocari Sweat in several regions. Data analysis was carried out using multiple regression to determine how much influence each variable had on purchasing decisions. The research method used was a survey with a purposive sampling technique. Data collected through questionnaires and analyzed using multiple regression to test the proposed hypothesis. The results of the study showed that online testimonials had a significant positive effect on purchasing decisions. Likewise, celebrity endorsers also had a significant positive effect. Simultaneously, both variables explain variations in purchasing decisions. The practical implication of this study is the importance of companies to utilize positive online testimonials and choose credible and appropriate celebrity endorsers.